Effect of mixing urea with zeolite and sago waste water on nutrient use efficiency of maize (Zea mays L.) - Omar, Latifah; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad (Academic Journals, 2011)
The efficiency of urea is poor due to the substantial amount of N lost to the atmosphere by ammonia volatilization. Thus, the objectives of this greenhouse study were to evaluate the effectiveness of mixing urea with zeolite and sago waste water on N, P and K uptake and their use efficiency in maize cultivation, and soil exchangeable ammonium, available nitrate, pH, exchangeable K, and available P contents. The treatments evaluated were: No fertilizer (T0), 2.02 g urea (T1), 2.02 g urea + 30 g zeolite + 7 L sago waste water (T2), 2.02 g urea + 40 g zeolite + 7 L sago waste water (T3), and 2.02 g urea + 7 L sago waste water (T4). Triple Super Phosphate (TSP) and Muriate of Potash (MOP) were used as sources of P and K for all the treatments except for T0. These fertilizers were applied twice that is 10 and 28 days after planting. Phosphorus and K requirements of the test crop were met by applying TSP and MOP (standard rate for the test crop) to plants of all the treatments except T0. The mixtures of sago waste water, and zeolite, with urea had significant effect on dry matter, N, P, K uptake and N, P, K use efficiency compared with urea without additives. These mixtures also significantly increased soil exchangeable ammonium, K, Ca, Mg, available P, and nitrate contents compared with urea without additives. Amending urea with sago waste water and peat soil water can reduce ammonia loss by encouraging formation of ammonium and nitrate over ammonia. Additionally, the mixtures ensure N, P, K uptake and their use efficiency while at the same time making soil ammonium, K, Ca, Mg, P, and nitrate available for plant use.